Fitness and ERP Indices of Cognitive Control Mode during Task Preparation in Preadolescent Children - Kamijo, Keita; Masaki, Hiroaki (Frontiers in Human Neuroscience, 2016)
A growing number of studies conducted over the past decade have demonstrated that greater aerobic fitness is associated with superior cognitive control in preadolescent children. Several studies have suggested that the relationship between fitness and cognitive control may be attributed to differential reliance on proactive versus reactive cognitive control modes. However, this contention has remained speculative, and further studies are needed to better elucidate this relationship. We designed the present study to test the hypothesis that use of cognitive control modes would differ as a function of childhood fitness. We compared performance of lower-fit and higher-fit children on a modified AX-continuous performance task, commonly used to examine shifts in the use of proactive and reactive control, along with cue-P3 and contingent negative variation (CNV) of event-related brain potentials (ERPs). Results indicated that higher-fit children exhibited greater response accuracy for BX (nontarget cue - target probe) relative to AY (target cue - nontarget probe) trials, whereas lower-fit children had comparable response accuracies for AY and BX trials. Because enhanced BX performance and impaired AY performance may be attributed to the proactive use of context information, these results suggest that greater childhood fitness is associated with more effective utilization of proactive control. Higher-fit children also exhibited larger cue-P3 amplitude and smaller CNV amplitude for BX relative to AY trials, with no such effect of trial type in lower-fit children. These ERP results suggest that greater fitness is associated with more effective utilization of cue information and response preparation more appropriate to trial type, supporting the behavioral findings. The present study provides novel insights into the relationship between fitness and cognition from the perspective of cognitive control mode during task preparation.